Gut microbiota development in the growing dog: A dynamic process influenced by maternal, environmental and host factors - Garrigues, Quentin; Apper, Emmanuelle; Chastant, Sylvie; Mila, Hanna (Frontiers in Veterinary Science, 2022)
Microorganisms of the gastrointestinal tract play a crucial role in the health, metabolism and development of their host by modulating vital functions such as digestion, production of key metabolites or stimulation of the immune system. This review aims to provide an overview on the current knowledge of factors shaping the gut microbiota of young dogs. The composition of the gut microbiota is modulated by many intrinsic (i.e., age, physiology, pathology) and extrinsic factors (i.e., nutrition, environment, medication) which can cause both beneficial and harmful effects depending on the nature of the changes. The composition of the gut microbiota is quickly evolving during the early development of the dog, and some crucial bacteria, mostly anaerobic, progressively colonize the gut before the puppy reaches adulthood. Those bacterial communities are of paramount importance for the host health, with disturbance in their composition potentially leading to altered metabolic states such as acute diarrhea or inflammatory bowel disease. While many studies focused on the microbiota of young children, there is still a lack of knowledge concerning the development of gut microbiota in puppies. Understanding this early evolution is becoming a key aspect to improve dogs’ short and long-term health and wellbeing.